Perengkahan n-Butana Menggunakan Katalis Nanopartikel Zeolit Alam Klaten - Kurniawan, Teguh; Muraza, Oki (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2018)
Increasing demand on olefins, high energy consumption of thermal cracking and oil depletion are the driving force to find new process to produce olefins. Catalytic cracking of n-butane is promising route to produce olefins. In this paper, we synthesized nanoparticle from natural zeolites by ball milling-recrystallization method and studied the effect of acid dealumination over the nanozeolites on the catalytic properties. Particle size was evaluated visually by using scanning electron microscope. X-Ray Diffraction analysis was performed to study zeolites phase and its crystallinity. Acid dealumination effect over nanosized mordenite on the acidity were evaluated by ammonia TPD and pyridine FTIR. Textural properties of zeolites were characterized by nitrogen physisorption at -196 oC. The catalysts were tested in a fixed bed reactor for n-butane cracking to olefins product. Various temperature conditions were applied ranging from 350 oC to 650 oC for n-butane cracking in a fixed bed reactor. Conversions of n-butane were 15% and 90% at 350 oC and 650 oC, respectively. Selectivity to olefins was increase from 1% at 350 oC to 47% at 650 oC.